Attractin Participates in Schizophrenia by Affecting Testosterone Levels - Li, Nan; Gao, Shuzhan; Wang, Shuang; He, Sijie; Wang, Jiayin; He, Luqingqing; Jiang, Dongya; Shi, Yun Stone; Zhang, Jianguo; Gu, Yuan; Chen, Tian; Kong, Mingjun; et al. (Frontiers in Cell and Developmental Biology, 2021)
Attractin (ATRN) plays an important role in neurodevelopment and immune response. Previous studies have found that the chromosome 20p13 on which ATRN is located has a strong correlation with schizophrenia. The clinical diagnosis of mental disorders mainly relies on Doctors’ judgment on the “abnormal” behaviors of the patients. To evaluate the correlation between ATRN and schizophrenia, we made atrn knockout zebrafish line and analyzed their behavior patterns. Adult atrn-/- zebrafish presented stronger attack behavior relative to wild type control in tracking analysis. We also found that testosterone level was elevated in these zebrafish. Transcriptome analysis showed that the expression of cyp51 and hsd17b7 in the testosterone synthesis pathway are up-regulated in the adult brain and larvae of atrn-/- zebrafish. We further analyzed the testosterone level of the 9008 patients and 247 healthy people (2018-2020) in Nanjing Brain Hospital. The male schizophrenia patients have more portion in low testosterone level compared to the control. But the majority of women with schizophrenia and bipolar disorder have higher testosterone levels. We then analyzed 14 schizophrenia patients with ATRN mutations have more proportion on abnormal testosterone level comparing to that of schizophrenia patients without ATRN mutations. In summary, ATRN may affect the behavior of organisms by affecting the formation of testosterone, which provides ideas for explaining the correlation between mental disorder and hormone levels.